IN VITRO, EX-VIVO, AND DISSOLUTION KINETIC STUDIES OF MOUTH-DISSOLVING SUBLINGUAL FILMS CONTAINING LOSARTAN POTASSIUM AND HYDROCHLOROTHIAZIDE - VINAYATA ATTAL; KRATIKA DANIEL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Sublingual films were designed for easy administration, rapid as well as slow drug absorption for obtaining controlled release action through the oral mucosa, bypassing the gastrointestinal tract and hepatic first-pass metabolism. This can result in a faster onset of action, enhanced bioavailability, and patient convenience since water isn’t required for administration. Films also offer precise dosing, enhanced drug stability, and targeted therapy for localized treatment within the oral cavity. These features make a non-invasive and painless alternative to injections, improving the patient experience. This paper focuses on in vitro and ex vivo activity using goat oral mucosa and the suitability of release kinetics using different kinetic parameters. Methods: Films were generated using a solvent casting method where a polymer, drug, plasticizers, and excipients were dissolved in a solvent to form a homogenous mixture. This mixture was poured into a petri dish, forming a thin layer. After controlled evaporation, the resulting film was cut to the desired size and shape and stored away from light and heat. Results: Ex vivo studies using goat buccal mucosa showed effective drug absorption. F4 batch was considered an optimized batch because it showed a release of 79.23±1.15% in 9 h in in vitro release study and ex vivo studies showed the highest permeation as compared to other batches and is found to be 96.54±1.23% in 9 h and the flux was calculated to be 0.975±1.15 mg h−1cm−2, 0.904±0.92 mg h−1cm−2, and 0.901 mg h−1cm−2 (Target flux 0.991 mg h−1cm−2).Two-way ANOVA suggested p<0.05. The drug release was best described by the Higuchi square root model, indicating a diffusion-controlled process. Conclusions: The film containing losartan potassium and hydrochlorothiazide offers a significant advancement in hypertension treatment. This approach boosts therapeutic outcomes and patient quality of life by overcoming demands associated with traditional oral dosage forms. Further research could extend the benefits of film to other medications and conditions, enhancing the field of drug delivery.